Exploration and identification of Anredera cordifolia morphological characters in the highlands and lowlands - Yaya Hasanah; Lisa Mawarni (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Hasanah Y, Mawarni L. 2020. Exploration and identification of Anredera cordifolia morphological characters in the highlands and lowlands. Biodiversitas 21: 2759-2766. Information about genetic diversity and relationships between accessions is very important in plant breeding programs, because with the availability of this information, it is easier to determine relationship between accessions that can be used as a basis for plant selection. The objective of the research was to evaluate the morphological characteristics and relationship of binahong or Anredera cordifolia (Ten.) Steenis) accessions in the lowlands and highlands. The study was conducted in Karo (highlands) and Medan (lowlands), North Sumatra, Indonesia, from May to August 2019. This research used a descriptive method. Before the survey and exploration are conducted, first a pre-survey was conducted by gathering information from key informants and other informants. The characteristic of morphological diversity A. cordifolia can be distinguished based on leaf color, stem shape, axillary tuber, rhizome, and the presence of flowers. The dendrogram relationship between accessions is based on a genetic similarity matrix using cluster analysis. Analysis of qualitative morphological characters revealed the existence of variability among A. cordifolia accessions. There is a far relationship relation between A. cordifolia plants in Karo and Medan with Eucludian range of 0.446 to 57.725, hence resulting in two clusters that show differences in the variation of A. cordifolia plants. There is a distant relationship relation with M4 and M7 accessions with a dissimilar distance of 57,725 and the closest relationship with accession K1 and K2 with a dissimilar distance of 0.446. Therefore, morphological characterization in the research is valuable to understand the variability of genetic of A. cordifolia accessions in the lowland and highland in North Sumatra.